Preparation, Purification and Spectral Properties of A New Thiourea Derivative Produced from Γ-Aminomycic Acid with A Thiourea Fragment of P-Hydroxybenzoic Acid - Khaydarova, Khulklar; Niyazov, Laziz (American Journal of Biomedicine and Pharmacy, 2026)
The article describes the synthesis of a new 1-(4-hydroxybenzoyl)-3-(3-carboxypropyl)thiourea by nucleophilic addition reaction between 4-hydroxybenzoyl isothiocyanate and γ-aminobutyric acid (GABA), the optimization of reaction conditions, the isolation and purification of the product, as well as its physicochemical and spectral characterization. The reaction was found to proceed in dimethylformamide or ethanol, in an inert (argon) environment, in the temperature range of 20-50 °C, without a catalyst or in the presence of a small amount of triethylamine, for 1-3 hours with a yield of 80.4%. The resulting compound is considered an important precursor in the development of penicillin analogues to overcome the instability of the β-lactam ring and resistance to β-lactamases, as well as in the synthesis of ligands for GABA-A and GABA-B receptors. This work proposes a simple, inexpensive, and industrially applicable method for synthesizing hybrid molecules based on thiourea.